KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH DALAM MENINGKATKAN PRESTASI AKADEMIK DI SDN 10 SERINDANG - Suha, Ana; Sukmawati, Sukmawati; Radiana, Usman (Universitas Tanjungpura, 2021)
AbstractThe form of this research is a qualitative approach. The subjects of this study were 1 principals and 11 teachers. Methods of collecting data through observation, interviews, documentation, and triangulation. While the data analysis used qualitative data analysis. While the validity of the data is tested in four ways, namely internal validity, transferability, dependability, and confirmability. The main findings in this study: (1) The principal has implemented interpersonal communication occurs directly between the principal and the teacher, close relationship in communication, teachers occur in a long time and the principals and teachers know each other's personal characteristics. (2) Barriers to interpersonal communication passed by the principal, namely time barriers, social media that does not support, physical influence between male teachers and female teachers, and the psychological influence of which is the age factor. (3) to overcome the principal's interpersonal communication barriers build a high empathy attitude towards the teacher's task, get used to being a good listener, repeat information that is not clear, then determine an effective time to communicate interpersonal. The conclusions in this study are the principal has implemented interpersonal communication in improving academic achievement at the school, Obstacles in the implementation of interpersonal communication that the Principal goes through consist of time constraints, media influences, physical influences, and psychological influences, the principal has overcome obstacles in interpersonal communication. Keywords: Academic Achievement, Interpersonal Communication